A method for calcining three-phase calcium silicate mineralized products by using lithium mica lithium extraction residue as mineralizing agent
Patent Information
- Application Number
- CN202311832965.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-28
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-12-28
AI Technical Summary
[0004]本发明提出一种以锂云母提锂渣作矿化剂烧制三相硅酸钙矿化制品的方法,旨在解决锂渣烧结时堵窑,以及现有CO2矿化驱动制品中制备成本高、CO2矿化速率慢、力学性能发展不足等问题
[0017]1、锂云母提锂渣作为胶凝材料,其碳化活性不足,而利用锂渣、电石渣和砂岩等固体废弃物按一定配比烧结,得到以硅酸二钙为主的CO2矿化驱动材料,碳化活性远高于未烧结生料;本发明提出了基于三相硅酸钙(即β-C2S、γ-C2S与C3S2)共存下的矿化制品的矿化活性时效匹配、协同设计的新思路,实现了锂渣、电石渣和砂岩等多元固废,以及γ-C2S、β-C2S与C3S2协同固碳,其中β-C2S能够提高碳化基体力学性能,γ-C2S能够提高熟料碳化反应活性,低钙矿物C3S2能够进一步降低烧成温度。
Smart Images

Figure CN117843315B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of solid carbon cementitious materials technology, specifically relating to a method for calcining triphase calcium silicate mineral products using lithium mica lithium extraction slag as a mineralizing agent. Background Technology
[0002] With the development of the lithium industry, lithium slag (LS) has increased dramatically, reaching over 1.2 million tons annually. If not effectively utilized, stockpiled LS not only occupies vast amounts of land but also pollutes the environment. Lithium primarily originates from spodumene and lepidolite ore. Lithium extraction from lepidolite ore is achieved through methods such as salt pressure cooking, producing slag containing silica, alumina, and a significant amount of sulfates, which can therefore be used as a mineralizing agent in the sintering process of low-calcium clinker. Secondly, cement is the world's second most consumed material, but cement production involves high energy consumption and high carbon dioxide emissions; therefore, reducing CO2 emissions from the cement industry is crucial. The cement industry has already undertaken significant efforts to reduce CO2 emissions, such as using clean energy to replace fuels and calcium-based raw materials, lowering sintering temperatures, and developing low-calcium clinker. Simultaneously, global industries emit large amounts of solid waste annually, with lithium slag, steel slag, fly ash, and calcium carbide slag being the most representative examples. Mineralization curing technology, which uses low-calcium clinker as the main carbonation cementitious material, can not only greatly reduce CO2 emissions, but also absorb a large amount of CO2 during the carbonation process and permanently seal it in the form of carbonates (such as CaCO3 / MgCO3).
[0003] In recent years, high-efficiency CO2 carbonization products using low-calcium silicate mineral C2S as the main carbonation cementing material have attracted widespread attention and extensive research from scholars and engineers both domestically and internationally due to their higher carbonization activity and unique self-pulverization advantage, which can reduce grinding energy consumption. However, there are still many problems to be solved in the preparation of dicalcium silicate by sintering lithium mica slag as a mineralizer. For example, during the sintering process, lithium mica slag can cause kiln blockage, and the calcium raw materials are mostly limestone, which generates a large amount of CO2 during sintering. Therefore, it is of great significance to use lithium slag, carbide slag, and sandstone to prepare a low-carbon CO2 mineralization-driven product based on dicalcium silicate for multi-element solid waste and synergistic carbon fixation. Summary of the Invention
[0004] This invention proposes a method for calcining three-phase calcium silicate mineralized products using lithium mica slag as a mineralizing agent, aiming to solve the problems of kiln blockage during lithium slag sintering, as well as the high preparation cost, slow CO2 mineralization rate, and insufficient mechanical properties of existing CO2 mineralization driven products.
[0005] To achieve the above objectives, the present invention specifically adopts the following technical solution:
[0006] This invention provides a method for calcining triphase calcium silicate mineral products using lithium mica lithium extraction slag as a mineralizing agent, comprising the following steps:
[0007] 1) Raw material ratio: Take lithium mica lithium extraction slag, calcium solid waste, silicon solid waste and flux iron oxide, mix them according to calcium-silicon molar ratio of 1.5-2.5, add water and ball mill to obtain slurry, dry the slurry to obtain raw material, wherein the ball milling speed is 300-400 rpm.
[0008] 2) Raw material preparation: Mix the raw material obtained in step 1) with anhydrous ethanol and press it into a blank;
[0009] 3) Raw material firing: The green body obtained in step 2) is calcined and cooled in the furnace to obtain clinker, wherein the calcination temperature is 1310-1350℃;
[0010] 4) Clinker mineralization: The clinker obtained in step 3) is added with water and pressed into a mineralized pre-product matrix, and finally carbonized to obtain the mineralized product. The CO2 pressure during the carbonization process is 0.1-0.3 MPa.
[0011] Preferably, the lithium mica slag from step 1) is used as a mineralizing agent, with an SO3 content greater than 20% and a total Na2O and K2O content greater than 10%.
[0012] Preferably, the amount of lithium mica slag added in step 1) is 2-6%.
[0013] Preferably, the calcium-based solid waste in step 1) is one or more of carbide slag, waste cement stone, papermaking sludge, and steel slag, with a CaO content greater than 60%.
[0014] Preferably, the siliceous solid waste in step 1) is one or more of sandstone, copper tailings sand, silica fume, rice husk ash, and waste glass, with a SiO2 content greater than 50%.
[0015] This invention regulates the calcium-silicon ratio of siliceous solid waste and calcareous solid waste by adjusting the lithium extraction slag from lepidolite, thereby controlling the carbonation characteristics of CO2 mineralization-driven products. The products are then subjected to CO2 mineralization curing. The mechanical properties of the high-efficiency CO2 mineralization-driven products are tested according to GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the degree of carbonation is evaluated using the lost-on-ignition calcium carbonate method.
[0016] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0017] 1. Lithium mica slag used as a cementing material has insufficient carbonization activity. However, by sintering solid wastes such as lithium slag, carbide slag, and sandstone in a certain proportion, a CO2 mineralization-driven material with dicalcium silicate as the main component is obtained, which has a much higher carbonization activity than unsintered raw materials. This invention proposes a new approach to the time-matching and synergistic design of mineralization activity of mineralized products based on the coexistence of three-phase calcium silicate (i.e., β-C2S, γ-C2S, and C3S2). This achieves synergistic carbon fixation of multi-component solid wastes such as lithium slag, carbide slag, and sandstone, as well as γ-C2S, β-C2S, and C3S2. Among them, β-C2S can improve the mechanical properties of the carbonized matrix, γ-C2S can improve the carbonization reaction activity of clinker, and the low-calcium mineral C3S2 can further reduce the firing temperature.
[0018] 2. Utilizing lithium slag as a mineralizing agent and non-carbonate calcium carbide slag for clinker calcination does not generate CO2, lowers the calcination temperature, and can absorb and solidify a large amount of CO2. Therefore, this invention, which uses lithium slag and non-carbonate solid waste to prepare a low-energy-consumption mineralized product based on dicalcium silicate, is of great significance.
[0019] 3. The unique and innovative aspect of this invention lies in using lithium slag as a mineralizing agent to sinter a low-calcium cementitious material. Lithium-mica slag contains a large amount of sulfides, and these sulfur compounds react with oxygen to form SO3. The SO3 entering the clinker reduces the viscosity of the liquid phase, while the self-pulverizing properties of γ-C2S effectively prevent sintering and kiln blockage caused by lithium slag. Furthermore, the Li in the lithium slag... + Na + Plasma can suppress the β-C2S crystal transformation and regulate the ratio of calcium silicate (i.e., β-C2S, γ-C2S and C3S2) in mineralized products, providing guidance for the preparation of low-energy-consumption and high-carbonation-activity mineralized products based on solid waste. Attached Figure Description
[0020] Figure 1 The compressive strength diagrams for Examples 1-3 and Comparative Example 1 are shown (Example 1 is 2-LS, Example 2 is 3-LS, Example 3 is 4-LS, and Comparative Example 1 is 0-LS).
[0021] Figure 2 The X-ray diffraction patterns of clinker and CO2 mineralization-driven products in Examples 1-3 and Comparative Example 1 are shown (left is the XRD pattern of clinker, right is the XRD pattern of CO2 mineralization-driven product).
[0022] Figure 3 The images show the microstructure of the carbonized products after carbonization for 24 hours in Example 2 and Comparative Example 1 (left: Comparative Example 1, right: Example 2).
[0023] Figure 4 The graphs show the changes in conductivity and pH value of the clinker suspension before and after the carbonization reaction of Examples 1-3 and Comparative Example 1.
[0024] Figure 5 The graphs show the temperature evolution curves of the matrix carbonization reaction in Examples 1-3 and Comparative Example 1 (left is the temperature rise curve of the carbonization reaction, and right is the cumulative normalized exothermic curve). Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with embodiments. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall apply. Reagents or instruments whose manufacturers are not specified are all conventional products that can be purchased commercially.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. The terminology used in this specification is for the purpose of describing particular embodiments only and is not intended to limit the invention. The term "and / or" as used herein includes any and all combinations of one or more of the associated listed items.
[0027] The composition of lithium mica slag, carbide slag, and sandstone used in the following examples is shown in the table below.
[0028] Table 1 Chemical composition of raw materials
[0029]
[0030]
[0031] Example 1
[0032] A method for preparing triphase calcium silicate mineral products by calcining lithium extraction slag from lepidolite as a mineralizing agent includes:
[0033] (1) Place the required raw materials, lithium mica lithium extraction slag, carbide slag, and sandstone, in an oven for drying for 3 hours at a temperature of 105°C for later use.
[0034] (2) After the raw materials are dried, the lithium mica lithium extraction slag, carbide slag and sandstone are ground for 2 minutes by a sample preparation machine and then passed through a 200-mesh sieve for later use.
[0035] (3) Take 2 parts of lithium mica slag, 67 parts of calcium carbide slag, 31.5 parts of sandstone and 1.5 parts of flux iron oxide and mix them (calcium-silicon molar ratio 1.95). After stirring evenly, mix with water (liquid-solid ratio 2:1) and stir again for a certain period of time to fully disperse the mixture in the aqueous solution. Then pour it into a ball mill jar for mechanical ball milling (ball mill speed set at 300 r / min for 24 h). The resulting slurry is dried at 80℃ to obtain raw material.
[0036] (4) Mix 100 parts of raw material with 20 parts of anhydrous ethanol evenly, press into a green body under a pressure of 30 MPa, then dry the green body and place it in a muffle furnace, heat it to 1330℃ at a rate of 10℃ / min, keep it at the temperature for 3h, and take it out after cooling to room temperature with the furnace to obtain CO2 mineralization driven clinker with self-pulverizing characteristics. Grind it and pass it through a 75μm sieve.
[0037] (5) The clinker was pressed into cylindrical test blocks of φ20mm×20mm with water (water-solid ratio of 0.16, test block molding pressure of 10MPa, holding time of 1min), carbonized for 2, 6, 12, and 24h, CO2 pressure of 0.2MPa, CO2 concentration of 99%, and then its mechanical properties were tested.
[0038] (6) The mechanical properties of the high-efficiency CO2 mineralization driven products were tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the degree of carbonation was tested by calcium carbonate loss on ignition method.
[0039] Example 2
[0040] A method for preparing triphase calcium silicate mineral products by calcining lithium extraction slag from lepidolite as a mineralizing agent includes:
[0041] (1) Place the required raw materials, lithium mica lithium extraction slag, carbide slag, and sandstone, in an oven for drying for 3 hours at a temperature of 105°C for later use.
[0042] (2) After the raw materials are dried, the lithium mica lithium extraction slag, carbide slag and sandstone are ground for 2 minutes by a sample preparation machine and then passed through a 200-mesh sieve for later use.
[0043] (3) Take 3 parts of lithium mica slag, 67 parts of calcium carbide slag, 31.5 parts of sandstone and 1.5 parts of flux iron oxide and mix them (calcium-silicon molar ratio 1.94). After stirring evenly, mix with water (liquid-solid ratio 2:1) and stir again for a certain period of time to fully disperse the mixture in the aqueous solution. Then pour it into a ball mill jar for mechanical ball milling (ball mill speed set at 300 r / min for 24 h). The resulting slurry is dried at 80℃ to obtain raw material.
[0044] (4) Mix 100 parts of raw material with 20 parts of anhydrous ethanol evenly, press into a green body under a pressure of 30 MPa, then dry the green body and place it in a muffle furnace, heat it to 1330℃ at a rate of 10℃ / min, keep it at the temperature for 3h, and take it out after cooling to room temperature with the furnace to obtain CO2 mineralization driven clinker with self-pulverizing characteristics. Grind it and pass it through a 75μm sieve.
[0045] (5) The clinker was pressed into cylindrical test blocks of φ20mm×20mm with water (water-solid ratio of 0.16, test block molding pressure of 10MPa, holding time of 1min), carbonized for 2, 6, 12, and 24h, CO2 pressure of 0.2MPa, CO2 concentration of 99%, and then its mechanical properties were tested.
[0046] (6) The mechanical properties of the high-efficiency CO2 mineralization driven products were tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the degree of carbonation was tested by calcium carbonate loss on ignition method.
[0047] Example 3
[0048] A method for preparing triphase calcium silicate mineral products by calcining lithium extraction slag from lepidolite as a mineralizing agent includes:
[0049] (1) Place the required raw materials, lithium mica lithium extraction slag, carbide slag, and sandstone, in an oven for drying for 3 hours at a temperature of 105°C for later use.
[0050] (2) After the raw materials are dried, the lithium mica lithium extraction slag, carbide slag and sandstone are ground for 2 minutes by a sample preparation machine and then passed through a 200-mesh sieve for later use.
[0051] (3) Take 4 parts of lithium mica slag, 67 parts of calcium carbide slag, 31.5 parts of sandstone and 1.5 parts of flux iron oxide and mix them (calcium-silicon molar ratio 1.92). After stirring evenly, mix with water (liquid-solid ratio 2:1) and stir again for a certain period of time to fully disperse the mixture in the aqueous solution. Then pour it into a ball mill jar for mechanical ball milling (ball mill speed set at 300 r / min for 24 h). The resulting slurry is dried at 80℃ to obtain raw material.
[0052] (4) Mix 100 parts of raw material with 20 parts of anhydrous ethanol evenly, press into a green body under a pressure of 30 MPa, then dry the green body and place it in a muffle furnace, heat it to 1330℃ at a rate of 10℃ / min, keep it at the temperature for 3h, and take it out after cooling to room temperature with the furnace to obtain CO2 mineralization driven clinker with self-pulverizing characteristics. Grind it and pass it through a 75μm sieve.
[0053] (5) The clinker was pressed into cylindrical test blocks of φ20mm×20mm with water (water-solid ratio of 0.16, test block molding pressure of 10MPa, holding time of 1min), carbonized for 2, 6, 12, and 24h, CO2 pressure of 0.2MPa, CO2 concentration of 99%, and then its mechanical properties were tested.
[0054] (6) The mechanical properties of the high-efficiency CO2 mineralization driven products were tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the degree of carbonation was tested by calcium carbonate loss on ignition method.
[0055] Comparative Example 1
[0056] A method for preparing triphase calcium silicate mineral products by calcining lithium extraction slag from lepidolite as a mineralizing agent includes:
[0057] (1) Place the required raw materials, carbide slag and sandstone, in an oven for drying for 3 hours at a temperature of 105°C for later use.
[0058] (2) After the raw materials are dried, the carbide slag and sandstone are ground separately for 2 minutes using a sample preparation machine and then passed through a 200-mesh sieve for later use;
[0059] (3) Take 67 parts of carbide slag, 31.5 parts of sandstone and 1.5 parts of flux iron oxide and mix them (calcium-silicon molar ratio 2.0). After stirring evenly, mix with water (liquid-solid ratio 2:1) and stir again for a certain period of time to fully disperse the mixture in the aqueous solution. Then pour it into a ball mill jar for mechanical ball milling (ball mill speed set at 300 r / min for 24 h). The resulting slurry is dried at 80℃ to obtain raw material.
[0060] (4) Mix 100 parts of raw material with 20 parts of anhydrous ethanol evenly, press into a green body under a pressure of 30 MPa, then dry the green body and place it in a muffle furnace, heat it to 1330℃ at a rate of 10℃ / min, keep it at the temperature for 3h, and take it out after cooling to room temperature with the furnace to obtain CO2 mineralization driven clinker with self-pulverizing characteristics. Grind it and pass it through a 75μm sieve.
[0061] (5) The clinker was pressed into cylindrical test blocks of φ20mm×20mm with water (water-solid ratio of 0.16, test block molding pressure of 10MPa, holding time of 1min), carbonized for 2, 6, 12, and 24h, CO2 pressure of 0.2MPa, CO2 concentration of 99%, and then its mechanical properties were tested.
[0062] (6) The mechanical properties of the high-efficiency CO2 mineralization driven products were tested in accordance with GB / T50081-2002 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete", and the degree of carbonation was tested by calcium carbonate loss on ignition method.
[0063] The results show that the raw materials for the high-efficiency CO2 mineralization-driven products obtained by the method of this invention are mostly solid waste (over 98%), the firing temperature during the preparation process is low and CO2 is not released, and the mechanical properties develop rapidly and the degree of mineralization is high after CO2 mineralization. Figure 1 As shown.
[0064] Figure 1The compressive strength diagrams for Examples 1-3 and Comparative Example 1 are shown (Example 1 is 2-LS, Example 2 is 3-LS, Example 3 is 4-LS, and Comparative Example 1 is 0-LS). The compressive strength test results show that the CO2 mineralization-driven products incorporating lithium slag exhibit high compressive strength after carbonization. Furthermore, compared to the CO2 mineralization-driven product in Comparative Example 1 without lithium slag (0-LS), when the lithium slag content is 3% (3-LS), the strength of the clinker reaches 85 MPa after 2 hours of carbonization, and 120 MPa after 24 hours of carbonization, representing an increase of approximately 50%. This demonstrates that the lithium slag extracted from lepidolite in this invention significantly improves the overall carbonization performance of the CO2 mineralization-driven material.
[0065] Figure 2 The X-ray diffraction (XRD) patterns of clinker and CO2-mineralized-driven products from Examples 1-3 and Comparative Example 1 are shown (left: XRD pattern of clinker; right: XRD pattern of CO2-mineralized-driven product). The figures show that when the lithium slag content is 0% (0-LS), the main mineral phases of the calcined clinker are γ-C2S and β-C2S. However, with the addition of lithium mica-derived lithium slag during calcination, the clinker mineral phases are γ-C2S, β-C2S, C3S2, and a small amount of C2AS.
[0066] Figure 3 The images show the microstructures of the carbonization products after 24 hours of carbonization for Example 2 and Comparative Example 1 (left: Comparative Example 1 (0-LS), right: Example 2 (3-LS)). As can be seen from the images, after 24 hours of carbonization, both produced well-crystallized calcite-type calcium carbonate. For 0-LS, the carbonization product consisted of calcium carbonate and a small amount of CSH gel, with the calcium carbonate particles simply mechanically interlocked. In contrast, the carbonization product of 3-LS contained more CSH gel. The silica gel generated by γ-C2S and the CSH gel generated by β-C2S together acted as a binder, tightly binding the calcium carbonate particles together.
[0067] Figure 4 The graphs show the changes in conductivity and pH value of the clinker suspension before and after the carbonization reaction in Examples 1-3 and Comparative Example 1. As can be seen from the graphs, comparing the clinker before and after CO2 introduction, the conductivity and pH value of the clinker rapidly increase and then tend to stabilize. Specifically, for 0-LS and 3-LS, before CO2 introduction, the ion dissolution rates of both were not significantly different and were both higher than those of 2-LS and 4-LS. After 5 minutes, with the introduction of CO2, the conductivity and pH value decreased rapidly, while 3-LS continued to ionize Ca. 2+ It reacts with CO2, and its conductivity gradually increases with the increase of CO2 introduction time. This is related to its high hydration activity due to the presence of more β-C2S. The conductivity of 0-LS is always lower than that of 3-LS at pH, indicating that lithium mica slag has a good effect on improving the carbonization reaction activity of CO2 mineralization driven materials.
[0068] Figure 5 The graphs show the temperature evolution curves of the matrix carbonization reaction in Examples 1-3 and Comparative Example 1 (left: temperature rise curve of carbonization reaction; right: cumulative normalized exothermic curve). As can be seen from the graphs, the carbonization reaction is most vigorous in the early stage, with a sharp increase in reaction temperature, reaching a peak temperature of approximately 90°C at 0-LS. Subsequently, the temperature rise curve decreases rapidly and stabilizes after 1 hour. This indicates that the compressive strength and carbonization activity of the clinker matrix after CO2 mineralization are closely related to the phase composition (γ-C2S, β-C2S, and C3S2). Lithium mica slag plays a crucial role in regulating the mineral phase ratio, CO2 mineralization activity, and the strength development of the constructed carbonized matrix in the calcined dicalcium silicate clinker system.
[0069] The embodiments described above are merely preferred embodiments of the present invention, and while the descriptions are specific and detailed, they are not intended to limit the present invention. It should be noted that various changes and modifications can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, or improvements made within the concept and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing triphase calcium silicate mineral products by calcining lithium mica slag as a mineralizing agent, characterized in that, Includes the following steps: 1) Raw material ratio: Take lithium mica lithium extraction slag, calcium solid waste, silicon solid waste and flux iron oxide, mix them according to calcium-silicon molar ratio of 1.5-2.5, add water and ball mill to obtain slurry, dry the slurry to obtain raw material, wherein the ball mill speed is 300-400 rpm; The lithium extraction slag from lepidolite is used as a mineralizing agent, with an SO3 content greater than 20%, a total Na2O and K2O content greater than 10%, and an admixture content of 2%-6%; The calcium-based solid waste is carbide slag, with a CaO content greater than 60%. The siliceous solid waste is sandstone with a SiO2 content greater than 50%. The flux, iron(III) oxide, accounts for 1.5% of the total mass of calcareous solid waste, siliceous solid waste, and flux. 2) Raw material preparation: Mix the raw material obtained in step 1) with anhydrous ethanol and press it into a blank; 3) Raw material firing: The green body obtained in step 2) is calcined and cooled in the furnace to obtain clinker, wherein the calcination temperature is 1310-1350℃; 4) Clinker mineralization: The clinker obtained in step 3) is added with water and pressed into a mineralized pre-product matrix, and finally carbonized to obtain the mineralized product. The CO2 pressure during the carbonization process is 0.1-0.3 MPa.
Citation Information
Patent Citations
Method for preparing cement from lithium slag
CN113072312A
High-performance hydration driving material as well as preparation method and application thereof
CN116023057A